?VISCOSITY COEFFICIENTS AND ACTIVATION PARAMETERS OF LANTHANUM CHLORIDE IN PU~E AND MIXED SOLVENTS AT DIFFERENT TEMPERATURES (Biological Sciences - PJSIR, 1998)
The measurement of viscosities of various solutions of' Lanthanum chloride in pure water, pure methanol and different percentages of water-methanol i.e. mixed solvents has been made at different temperatures 298, 303, 308 and 313°K. The viscosity coefficients have been determined by using the Jone-Dole equation and found to vary with temperature and solvent compositions. The activation parameters have been determined in pure water, pure methanol and in 54% aqueous methanol at 298, 303 and 313°K. The .salt has been found to be a structure breaker.